Operative findings of the migrated stent into the abdominal cavity following endoscopic ultrasound‐guided hepaticogastrostomy: Anchoring force of a novel self‐expandable metal stent with an anti‐migration system (with video). (19th January 2022) - Koga, Takehiko; Ishida, Yusuke; Hirai, Fumihito
Abstract : Koga et al report an emergency surgery for stent migration during endoscopic ultrasound‐guided hepaticogastrostomy, which revealed the strong anchoring force of a stent with a spring‐type stopper as an anti‐migration system at the proximal end. The stent could not be pulled out of the stomach wall and was removed via gastrotomy.